Pengaruh Beban Kerja, Job Burnout, Dan Konflik Peran Terhadap Tingkat Stres Kerja Pada Karyawan PT. Adhi Makmur Oenggoel Insani - Lara Sagitha Odini; Anton Prasetyo (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
This study aims to determine the effect of workload, job burnout and role conflict on work stress. data collection was carried out through distributing questionnaires to 48 respondents. Data collection techniques by distributing questionnaires. The analysis used is the validity test, reliability test, classic assumption test, multiple linear regression analysis test and the coefficient of determination. The analysis technique used is the help of the SPSS analysis program Version 25 for Windows. The results obtained in this study indicate that the variable workload, job burnout and role conflict have a simultaneous effect on work stress. The workload variable has a significant effect on work stress, the job burnout variable has a significant effect on work stress, while the role conflict variable has a significant effect on work stress.